Pathogenetic value of scd40l in elderly and senile patients with stable angina: alternative for c-reactive protein - Kraidashenko, O. V.; Shalmina, M. A. (Zaporozhye Medical Journal, 2013)
The level of C-reactive protein (CRP), soluble form of Cd40L and ischemic episodes were studied in 108 patients with stable angina II-III FC of elderly and senile age, and also in 33 practically healthy persons. It was shown the increase of scd40l level and CRP in blood of the basic group of patients. According to the cross-correlation analysis strong correlation was noticed for the indicated indexes, and also for the duration of ischemic changes of myocardium for the elderly and senile patients with stable angina.